Education and Training Needs of Health Care Professionals in the Philippines Encountering Patients with Lung Oligometastatic Cancers - Daphne J. Valmonte; Naa Kwarley Quartey; Fatima Gutierrez; Janel Mendoza; Janet Papadakos; Meredith Giuliani (Current Oncology)
This study aimed to examine the education and training needs of health care practitioners (HCPs) in the Philippines who encounter lung oligometastatic cancer patients. Lung oligometastatic disease is among the most common sites for cancer spread and has the most established practices for treating oligometastases. A modified version of the Hennessy–Hicks Training Needs Assessment Questionnaire was administered online to HCPs working in private and public centers in the Philippines. HCPs were recruited via purposive sampling. Twenty-seven HCPs completed the questionnaire (47% response rate). Respondents were mostly female (59%) and between the ages of 30 and 39 years (70%). Three-quarters (74%) were consultants, and most respondents were radiation oncologists (44%) or medical oncologists (30%). Medical oncologists rated Management/Supervisory Tasks (mean = 1.42) as their highest area of training need while radiation oncologists rated Clinical Tasks (mean = 1.30) as their highest training need. Pulmonologists (mean = 0.60) and other specialists (mean = 1.00) rated Administration tasks as their top area of training need. The clinical task-related category was rated the highest need among the continuing medical education topics. This study provides valuable insights for the implementation and advancement of a comprehensive curriculum in clinical oncology, specifically designed to enhance the administrative, clinical, and research capacities of oncologists who encounter oligometastatic lung disease in the Philippines.